PERTANGGUNGJAWABAN PIDANA ANAK DIBAWAH UMUR SEBAGAI PELAKU TINDAK PIDANA NARKOTIKA (Studi Putusan Pengadilan Nomor 366/Pid/Sus-Anak/2014/PN. Pdg) - Eryco Syanli Putra; Madiasa Ablisar; Marlina Marlina; Suhaidi Suhaidi (Universitas Sumatera Utara, 2017)
ABSTRACT Differing views of judges in giving legal for children the doers also be the basis of punishment is given or not given to children the doers. In fact, over the many decisions of the judges are more inclined to give a prison sentence than provide rehabilitation or other penalties for child offenders narcotic crime. This fact is very unfortunate given the children who are still growing and need the attention of all parties, favors given physical punishment of the child's psyche recover from the addiction and drug dependence. Issues raised in this study, namely how the rule of law against children as a criminal narcotics, forms of legal protection provided to the child offender narcotics, and criminal liability of children criminal narcotics Court Decision No. 366 /Pid/ Sus-Kids/2014/PN. Pdg. To find answers to these problems, this study used types of normative legal research is a descriptive analysis, which the normative legal research using secondary data as the main data with munggunakan techniques of data collection is done by means of a literature study (library reseacrh), as well as data analysis method qualitative data analysis. The data analysis is meant by an idea, facts obtained will be analyzed carefully to address the problem Keywords: Criminal Liability, Children, Crime, Narcotics.